MATURITY AND SPAWNING OF THE ANCHOVY, THRISSINA BAELAMA (FORSKAL) FROM THE ANDAMAN SEA - Marichamy, R (Indian Journal of Fisheries, 2011)
The occurrence of mature and spent specimens of Thrissina baelama in different sizegroups indicated that the fish matures at an average length of 117 nun (TL). This is supportedby the results obtained from the study of ponderal index. While the immaturefemales showed a more or less direct relationship between 'Kn' values and feeding activity,the mature females showed some deviations during certain months. The study of ova diametershas shown that the species spawns twice in a year. Spawning appears to be of shortduration and the whole stock of mature ova measuring 0,57-0.84 nun in diameter areextruded during the spawning. Two spawning seasons in a year were observed and thesecoincided with the two monsoons, during July-August and late November-January.Fecundity ranged between 1171 and 3356 ova in a fish size range of 110-127mm. Logarithmicregressions described the relationship between fecundity and weight of fish andfecundity and weight of ovary.